The impact of patent expiry on drug prices: insights from the Dutch market - Simon van der Schans; Gert T. Vondeling; Qi Cao; Simon van der Pol; Sipke Visser; Maarten J. Postma; Mark H. Rozenbaum (Journal of Market Access & Health Policy)
Background: Currently literature on the impact of patent expiry on drug prices is lacking. Objective: To determine the impact of patent expiration and generic entry on drug prices in the Netherlands. Methods: Prescription and price data from 1999 up to and including December 2016 were collected from two national databases. The overall price ratio of drugs prices up to 48 months after patent expiration was compared to the price in the month before expiry. Sub-analyses were performed to provide insights in generic uptake, length of market exclusivity and price development for originators and generics separately. Results: In total 250 drugs faced patent expiration during the study period. Forty-eight months after patent expiration the median price ratio decreased to 0.59 (IQR = 0.23–0.86) compared to the month prior patent expiry. Major differences in price developments were observed depending on the level of revenue prior to patent expiration and the time of patent expiration with ratios ranging from 0.08 (IQR = 0.07–0.16) to 0.81 (IQR = 0.62–0.97). Prior to patent expiry, the price decreased by 2.3% annually while having market exclusivity for 11.3 years on average. Conclusion: This study showed that the median drug price after patent expiration decreased by 41% after 4 years. The results of this study can be used to provide more reliable estimates on drug prices over its lifecycle and can be implemented in economic evaluations to inform the cost-effectiveness and long-term budget impact of new drugs.